Beyond the positive glow: how school climate inadvertently challenges mental health by modifying the relationship between BMI and depression in adolescents - Jiang, Ling; He, Qianyun; Chen, Chaonan (Frontiers in Psychology, 2025)
IntroductionAdolescence is a critical period for developing body esteem, shaped by physical changes and societal aesthetics, significantly impacting mental health. The relationship between body mass index (BMI) and depression warrants further exploration of mediating and moderating factors.MethodsA sample of 1,639 rural Chinese adolescents completed questionnaires. Mediation and moderation analyses were performed using SPSS 19.0.ResultsThe results showed that body esteem mediated the relationship between underweight status and depression, as well as the relationship between overweight status and depression among boys. Among girls, body esteem only mediated the relationship between underweight status and depression. Moreover, a positive school climate diminished the protective role of body esteem against depression for both boys and girls. It also strengthened the positive association between underweight status and body esteem for boys but weakened the negative association between underweight status and depression for girls.DiscussionAlthough a positive school climate correlates with better mental health, it may inadvertently reinforce harmful body esteem standards, highlighting the need for gender-specific approaches in school policies and interventions.